Evaluating Employee Protection at a State-Owned Indonesian Enterprise - Arya Wiranti, Widya; Putra Pratama, Andika (The Indonesian Journal of Business Administration, 2016)
Abstract - PT. Kereta Api Indonesia (Persero) is currently in the process of renewing the Collective Bargaining Agreement between the Management and the Trade Unions. The main issue is the extent to which PT. Kereta Api Indonesia (Persero), and more specifically the Collective Bargaining Agreement of PT. Kereta Api Indonesia (Persero), has applied ethical principles that have been endorsed internationally. Studying employee protection is important because employees are arguably the most im[portant company’s assets that would drive performance. This final project is aimed to find out how internationally recognized ethical principles in terms of employee protection have been applied at PT Kereta Api Indonesia (Persero) and to propose an improved content of the Collective Bargaining Agreement that incorporates findings from this research to be considered by PT. Kereta Api Indonesia (Persero). This final project reviewed about the employee protection in PT Kereta Api Indonesia (Persero) and UN Global Compact is chosen as the international ethical standard. The result is found that there is significant difference between D1 and D2 units in their perception of employee protection. There is difference of employee perception on employee protection especially for the efforts of handling human rights abuses and knowledge for helping and facilitating to fulfill of human rights abuse reviewed based on units. Two issues that cause significant differences in perception on employee protection in D1 and D2 unit are related to the knowledge (cognitive) and the action (conative) of the company with regard to handling the human rights abuses. It is proposed that the company make articles that discussed about woman employees to protect them from human rights abuses and elimination of forced labour. It is recommended that PT. KAI establish better industrial relations between trade union and management by communicating rights that want to fight for and that PT. KAI invite activists from the trade union to be held national working meeting (Rapat Kerja Nasional) about labor issues to support the objectives of trade union itself. Keywords: employee protection, human right